Comparison of anaerobic sludge granules from different wastewater plants with respect to granule size, substrate degradation and methanogenic community - Andrén, Jonathan (2018)
Within the objective to replace fossil fuel with sustainable sources there is a growing pressure to advance such development. Anaerobic digestion (AD) is beneficial not only as a waste management technology, but also to recycle organic waste into methane which can be used for heating, production of electricity or vehicle fuel. Although the anaerobic digestion for biogas production has been used and refined at a larger scale for several decades the system is susceptible to perturbations due to sensitivity of the degradation process. The process of degrading organic waste anaerobically is a complex process involving many trophic groups of microorganisms in a series of degradation steps, each step decomposing the substrate further. The most sensitive group are the methanogens, which come exclusively from the domain Archaea and produce methane. Because they are easily inhibited they are often rate limiting in the degradation process.